Antecedents of the effectiveness of entrepreneurship policy: An integrated framework - Mingyang Zhang; Wei Zhang (PLoS ONE, 2026)
By employing grounded theory method to conduct in-depth interviews, this paper argues that policy formulation, scientific and technology support, legal safeguards, policy implementation, and social environment are the major factors to influence the effectiveness of entrepreneurship policy of government, and thus comprehensively form an “effectiveness-testing” model to further analyze the pathway and internal mechanism. The findings show that these factors have an important effect on the effectiveness of entrepreneurship policy of government together with different functions. The findings are of great theoretical and managerial implications for perfecting and developing entrepreneurial management theory, public policy evaluation, and entrepreneurship policy management, as well as promoting local entrepreneurship and innovation activities.